The Noom mindset : learn the science, lose the weight. (Simon Element, 2022)
"The Noom Mindset, created by the leading digital health company that has helped millions achieve their weight and health goals, deconstructs habits around the core drivers of body weight: what we eat and how much we move. You'll discover how your habits around eating and weight management are impacted by your own self-confidence, stress, habits, lifestyle choices, and the rollercoaster of motivation (yes, it's supposed to go up and down). Best of all, you'll learn skills that can be applied to any behavior you want to change, habit you want to break, or life you want to create."--